Garden centipede Scutigerella immaculata Newport, 1845 - An arthropod pest for the vegetable in Da Lat, Vietnam - Chau, Nguyen Ngoc (Academia Journal of Biology, 2015)
Symphylans also known as garden centipedes or pseudocentipedes were identified with scientific name as Scutigerella immaculata Newport, belonging to family Scutigerellidae, class Symphyla, subphylum Myriapoda and phylum Arthropoda.  Symphyla are small, cryptic myriapods without eyes and without pigment. The body is soft and generally mature body length (sample collected from Da Lat)  with 2.5 - 8 mm.  Morphologically, symphylans body is consists of three parts as head, trunk and tail. The head has a pair long, segmented antennae, a postantennal organ, three pairs of mouthparts: mandibles with the long first maxillae and a second pair of maxillae which are fused to form the lower lip or labium of the mouth. The disc-like organs of Tömösváry are attached to the base of the antennae. The trunk comprises  of 15-24 segments and they are protected by overlapping dorsal plates. The first segment is large and usually provided with a pair of legs, the last segment considered as "tail" is moderately slender, lacks legs and possesses a pair of cerci. Immature symphylans with six pairs of legs on hatching, but over a lifetime of several years, add an additional pair at each molt until the adult instar with twelve pairs of legs. Symphylans breathe through a pair of spiracles on the sides of the head. These are connected to a system of tracheae that branch through the head and the first three segments of the body only. The genital opening is on the fourth segment body, but they do not copulate. S. immaculata is characterized by a distinctly emarginated posterior margin of the second scutum of the trunk and by the homogeneity of the setae on the second scutum. Biotics: In general, symphylans  are soil-dwelling in surface layer and consume decaying vegetation, but they can cause considerable damage for vegetable crops by the consuming seeds, roots, and root hairs in cultivated soils. The garden centipedes are considered as an important pest causing damages for green vegetable, flowers, cherry and they commonly occurred in Da Lat (Lam Dong province), so far. For integrated management of garden centipedes, there are some practice measures recommended as the sampling for threshold evaluation, then use appropriate tillage techniques, such as soil processes, crop rotation, application of chemical pesticides or some selected biological agents. Among these, the soil preparation before planting based on making compressed soil with flatten surface is considered simple measures and workable as possible to reduce the density of garden centipede in soil top layer that to be comfortable for growth crops .